Study on the Seismic Performance of Strengthened Reinforced Concrete Columns Based on the Experiment. (7th January 2021) - Sun, Yanhua; Zhang, Xiaohu
Abstract : The seismic performance of reinforced concrete (RC) columns strengthened using steel bar/wire mesh mortar (SWM) was investigated. A comparative experimental study was performed by taking nine RC square columns strengthened with SWM and steel bar mat mortar (SM) under pseudostatic test. The effects of strengthening method and test parameters on the seismic bearing capacity, ductile deformation, and failure mode of all columns were tested and analyzed. The results show that SWM-strengthened columns can experience more cyclic loading times before the failure than SM-strengthened columns under the same axial load ratio, and the energy dissipation capacity and seismic bearing capacity of SWM-strengthened columns were higher on average than that of SM-strengthened columns by 62.3% and 73.66%, respectively, proving that the strengthening method has a good application in engineering practice.